2022
DOI: 10.1155/2022/9328160
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Key Genes and Pathways in Multiple Sclerosis Based on Weighted Gene Coexpression Network Analysis and Long Noncoding RNA-Associated Competing Endogenous RNA Network

Abstract: Objective. Multiple sclerosis (MS) is an autoimmune disease of the central nervous system characterized by chronic inflammation and demyelination. This study is aimed at identifying crucial genes and molecular pathways involved in MS pathogenesis. Methods. Raw data in GSE52139 were collected from the Gene Expression Omnibus. The top 50% expression variants were subjected to weighted gene coexpression network analysis (WGCNA), and the key module associated with MS occurrence was identified. A long noncoding RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Furthermore, the treatment of these cells with a common MS therapy can restore the levels of some of these RNAs, suggesting that the dysregulated polyadenylation may have pathogenic consequences (LaCava et al ., 2005). A study by Hao et al ., (2022) also showed that hub genes targeted by long non-coding RNAs (lncRNAs) and competing endogenous RNAs (ceRNAs) functioned in ribosomal processes. In addition, gene set enrichment analysis also showed that highly expressed hub genes were associated with base excision repair.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the treatment of these cells with a common MS therapy can restore the levels of some of these RNAs, suggesting that the dysregulated polyadenylation may have pathogenic consequences (LaCava et al ., 2005). A study by Hao et al ., (2022) also showed that hub genes targeted by long non-coding RNAs (lncRNAs) and competing endogenous RNAs (ceRNAs) functioned in ribosomal processes. In addition, gene set enrichment analysis also showed that highly expressed hub genes were associated with base excision repair.…”
Section: Discussionmentioning
confidence: 99%
“…that by following similar signaling pathways, the possible and similar effect of this LncRNA in MS can also be addressed. Other mRNAs examined include: ZMAT3, CCDC113, CMPK1, MCC, KCNK2, KCTD15, PIM1, GJA1, TMED5, BMPR1B, WEE1, CYBRD1, MAPK1, CRKL, PHKA1, DICER1, SEMA7A, RRAGD, ABHD17C, TOB1, FOXP4, ADD3, CMTM4, TGFBR3, ARHGEF26, SEMA6D, PREX2, GABRB1, PDLIM5, HNRNPF, RHOQ, ANKFY1, USP46, MTSS1, UXS1, PPP2CB, NOTCH2, FGFRL1, ZNF711, ROCK1, GNG12, CTSA, SUN2, SMAD1, LONRF1 and from Among the key LncRNAs investigated in multiple sclerosis disease, we can mention C17orf82, BOLA3-AS1, RBM26-AS1, RBMS3-AS3, CRNDE, FAM13A-AS1, VENTXP1 according to the studies of Dr. Hao and colleagues in 2022 (22).…”
Section: Discussionmentioning
confidence: 99%
“…Different RNAs will form multiple regulatory relationships, which will eventually form a ceRNA network. Currently, studies are being conducted on the pathogenesis of ceRNA-related diseases, and various ncRNAs (e.g., lncRNAs, miRNAs, circRNAs) and ceRNA networks constructed from differentially expressed ncRNAs have been shown to be related to the pathogenesis of various autoimmune diseases (20)(21)(22)(23), further illustrating the interconnection between different RNA molecules and the regulation of gene expression. The construction of ceRNA regulatory networks is of great importance to further understand the functions of ncRNAs.…”
Section: Introductionmentioning
confidence: 99%